Benchmark simulations of flow past rigid bodies using an open-source, sharp interface immersed boundary method. (28th June 2019) - Senturk, Utku; Brunner, Daniel; Jasak, Hrvoje; Herzog, Nicoleta; Rowley, Clarence W.; Smits, Alexander J.
This study reports benchmark results for a new immersed boundary method based finite-volume solver within the framework of the open-source toolbox foam-extend 3.2. The immersed boundary formulation uses a discrete forcing approach based on a weighted least squares approximation that preserves the sharpness of the boundary. Five test cases with increasing complexity are used. Results are also presented for the flow past a low-aspect-ratio plate that pitches about its leading edge at a Reynolds number of 2000. Force coefficient results are compared with available experimental and computational data. The results show that foam-extend 3.2 appears to be a promising open-source tool for solving flows with steady and unsteady immersed boundaries.